EXPLORING THE USEFULNESS OF GAMES IN DEVELOPING THE LEARNERS’ VOCABULARY: Vocabulary Teaching in Middle School - BENMEHIRIS Mohammed; SEDDIKI Med Cherif (University of Ammar Theledji -Laghouat, 2021)
This study attempts to determine the role of educational games on the teaching of English vocabulary to young learners. Vocabulary is challenging since it plays such an important part in assisting language learners in achieving proficiency in any language. In fact, they have a lot of trouble learning new things. As a result, their teachers should be aware of the ways students employ to tackle these challenges and improve their foreign vocabulary knowledge. This study looks at educational games as a valuable tool for examining effective vocabulary improvement through entertainment. Educational games can be a fascinating way for students to become familiar with new words, consolidate lexical items, and memorize them. In this case, a descriptive study is conducted by assessing teachers' opinions and attitudes toward educational games as a strategy of teaching vocabulary. It is founded on their perspectives, which were gathered through a questionnaire and observation. This study used a learner-centred approach, in which I observed students for three months, before, during, and after they participated in the instructional game. The main goal is to see how useful language games are for learning new things and using them. The results demonstrated that this technique was helpful in boosting the vocabulary knowledge of EFL middle school students. They demonstrated that they had memorized nearly all of the unfamiliar terms they had seen in the early sessions. They were also highly motivated and enthusiastic. As a result, it is suggested that educational games be employed to teach vocabulary.